PROTECTED AREAS – CHANCE OR BARRIER FOR FOOD QUALITY IN CASE OF AGRICULTURE IN POLAND - Iwacewicz Orlowska, Anna (Economics of Agriculture, 2014)
The main aim of this paper is to present the relation between the state of the natural environment and the food quality produced on a given area. The two groups of analysed business activities are ecological farms and eco-friendly food processing plants. In the work, the author conducted a comparative analysis of the Polish voivodships with large and small shares of valuable natural areas in the total area of the voivodship in relation to the ecological farms and eco-friendly food processing plants.